TDHF Theory and Its Extensions for the Multinucleon Transfer Reaction: A Mini Review - Sekizawa, Kazuyuki (Frontiers in Physics, 2019)
Time-dependent Hartree-Fock (TDHF) theory has been a powerful tool in describing a variety of complex nuclear dynamics microscopically without empirical parameters. In this contribution, recent advances in nuclear dynamics studies with TDHF and its extensions are briefly reviewed, along the line with the study of multinucleon transfer (MNT) processes in low-energy heavy-ion reactions. The latter processes lie at the core of this Research Topic, whose application for production of extremely neutron-rich nuclei has been extensively discussed. Having in mind the ongoing theoretical developments, how microscopic theories contribute to the future MNT study is envisaged.